Development of a Company Profile Application Prototype as a Digital Promotional Medium for PT Harmoni Persada Travel Company - Mugia Mutla Hara Atasyriqi; Farid Fadhilah Rochdiana; Hendra Gunawan (LP2M IAIN Palopo, 2026)
The digital transformation of the tourism industry demands a structured promotional platform for SMEs competing in the digital-native market. This study developed a prototype company profile application for PT Harmoni Persada Travel using a Research and Development (R&D) methodology with a prototype approach. The population included company stakeholders and potential users, with a purposive sampling of 10 respondents. Data collection used interviews, observations, document analysis, and a System Usability Scale (SUS) questionnaire supplemented by thematic analysis of open-ended feedback. The results showed strong prototype usability: 88% satisfaction with visual appeal, 85% ease of navigation, and 84% feasibility of development. The prototype successfully integrated the company profile, tour packages, destination gallery, basic chatbot, and contact using Figma with a consistent brand identity design. Conclusion: The structured R&D methodology enables travel SMEs to shift from conventional promotions to a professional digital platform, improving their competitive position.